2012
DOI: 10.1590/s0482-50042012000300005
|View full text |Cite
|
Sign up to set email alerts
|

Validade e confiabilidade da versão em português do American Shoulder and Elbow Surgeons Standardized Shoulder Assessment Form

Abstract: Introduction: The American Shoulder and Elbow Surgeons Standardized Shoulder Assessment Form (ASES), often used in research in Brazil, although translated and adapted to the Portuguese language, had not had its validity and reliability tested yet. Objective: To assess the validity, reliability, and internal consistency of the ASES-PT for shoulder dysfunction. Materials and methods: Fifty individuals (26 women; mean age, 39 ± 13 years) participated in the validity assessment, and 38 (19 women; mean age, 37 ± 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 25 publications
0
15
0
4
Order By: Relevance
“…The ASES shoulder score is one of the most common PROMs used in shoulder research 12,19,26 and has been validated for such use. 17,20,23 Many institutions have adopted routine, periodic collection of the ASES score to provide a consistent assessment of clinical success, a basis for scientific investigations of treatment methods, and documentation of the functional status of the shoulder. This commitment requires significant institutional resources and patients' time.…”
Section: Discussionmentioning
confidence: 99%
“…The ASES shoulder score is one of the most common PROMs used in shoulder research 12,19,26 and has been validated for such use. 17,20,23 Many institutions have adopted routine, periodic collection of the ASES score to provide a consistent assessment of clinical success, a basis for scientific investigations of treatment methods, and documentation of the functional status of the shoulder. This commitment requires significant institutional resources and patients' time.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported a comprehensive analysis of the psychometric properties of this instrument, such as internal consistency, measurement error, construct validity and floor and ceiling effects. Furthermore, Moser et al 35 analyzed internal consistency, convergent validity and reliability of the Brazilian version of the American Shoulder and Elbow Surgeons (ASES) score. Adequate results that support the utilization of both scores were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these questionnaires are applied in specific situations and disorders of the shoulder, and for overall evaluation of the upper limb. [18][19][20] The semantic validation and content of the Brazilian SRQ was obtained and revealed only a few adjustments in the areas of pain, daily activities and in sports and leisure. The authors of the Dutch version of the SRQ also made some adjustments in some areas.…”
Section: Discussionmentioning
confidence: 99%